The application of distributed virtual machines for enterprise computer management: A two-tier network file system for image provisioning and management - Aguiar, César S. [UNESP]; Cruz, Daniel I. [UNESP]; Spolon, Roberta [UNESP]; Cavenaghi, Marcos Antônio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In order to simplify computer management, several system administrators are adopting advanced techniques to manage software configuration of enterprise computer networks, but the tight coupling between hardware and software makes every PC an individual managed entity, lowering the scalability and increasing the costs to manage hundreds or thousands of PCs. Virtualization is an established technology, however its use is been more focused on server consolidation and virtual desktop infrastructure, not for managing distributed computers over a network. This paper discusses the feasibility of the Distributed Virtual Machine Environment, a new approach for enterprise computer management that combines virtualization and distributed system architecture as the basis of the management architecture. © 2008 IEEE.
Keywords: Computer network management; Distributed system; GRID; Virtual machines; Distributed system architecture; Distributed virtual machine; Hardware and software; Management architectures; Network file system; New approaches; Server consolidation; Software configurations; System administrators; Tight coupling; Virtual machining; Virtualization; Computer applications; Computer architecture; Computer hardware; Computer software; Computer systems; Computers; Costs; Distributed computer systems; Finance; Management; Microcomputers; Word processing; Computer networks